METABOLIC THERAPY EFFECTS ON CORONARY BLOOD FLOW IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - V. B. Simonenko; A. P. Golikov; A. A. Spassky (Российский кардиологический журнал, 2010)
Pharmaceutical treatment of coronary heart disease (CHD) should be able to solve the key task – reduction of myocardial oxygen demand, or improvement of oxygen supply via vasodilatation. Currently, metabolic therapy of CHD is of particular interest, since it can reduce myocardial oxygen demand and substantially increase the effectiveness of oxygen utilisation in myocardial ischemia settings. The study was aimed at investigating the effectiveness of pre-hospital therapy with a cytoprotector mexicor, with subsequent intracoronary mexicor administration in the first hours of acute myocardial infarction (AMI). In total, 112 AMI patients, hospitalised no later than 4 hours after AMI onset, were included in the study. Successful angioplasty of infarct-related coronary artery (IRCA) and intracoronary administration of a cardio-protector mexicor were associated with a substantial improvement in clinical effectiveness of coronary blood flow normalisation and prevention of myocardial reperfusion injury.